Tactical and shooting variables that determine win or loss in top-level in water polo - Vila, M. H.; Abraldes, J. A.; Alcaraz, P. E.; Rodriguez, N.; Ferragut, C. (International Journal of Performance Analysis in Sport, 2011)
The aims of this study were: 1) determine if there is a difference in the efficacy and velocity of shots between winning and losing teams 2) analyse the relationship between efficacy values according to the particular microsituations (even, power play, transition and penalty) and between winners and losers in disputed games. Seventy-two male games that formed part of the 2008 European Championship and the 2009 World Championship have been analysed. Efficacy coefficients were used to assess all of the microsituations of the game that ended with a shot to obtain efficacy values. The results presented significant differences between winning and losing teams in terms of the coefficients of definition and resolution of shots, and in the coefficient of resolution and detention of shots to goal in both championships. It could be said that the efficacy values that determine the difference between winning and losing teams are those that make reference to the accuracy of the shot. The penalty microsituation of reference is not a determining factor in the winner or loser status of a team. No differences exist in the speed of shot between winning and losing teams within the same championship but they do exist between championships.